2009
DOI: 10.1176/ps.2009.60.11.1522
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Risk of Future Violence Among Forensic Psychiatric Inpatients With the Classification of Violence Risk (COVR)

Abstract: The study provides the first independent validation of the COVR and evidence of the usefulness of the COVR in predicting harmful behavior in forensic inpatient settings in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Based on this, researchers have developed actuarial risk assessment tools to aid clinicians in evaluating risk of violent behavior in practice (Douglas, Cox et al, 1999; Gardner, Lidz, Mulvey, & Shaw, 1996a, 1996b; McNiel, 1998). Examples include the Violence Risk Appraisal Guide (VRAG) (Quinsey, Harris, Rice, & Cormier, 2006), HCR-20 (Douglas, Ogloff, Nicholls, & Grant, 1999; Douglas & Webster, 1999), and Classification of Violence Risk (COVR) (Monahan et al, 2005; Snowden, Gray, Taylor, & Fitzgerald, 2009; Steadman et al, 2000). Thus, clinicians providing mental health treatment to civilians now have at their disposal a substantial evidence-base evaluating risk of engaging in future violence (Heilbrun, 2009; Otto, 2009).…”
Section: Improving Risk Assessment Of Violence Among Military Veteranmentioning
confidence: 99%
“…Based on this, researchers have developed actuarial risk assessment tools to aid clinicians in evaluating risk of violent behavior in practice (Douglas, Cox et al, 1999; Gardner, Lidz, Mulvey, & Shaw, 1996a, 1996b; McNiel, 1998). Examples include the Violence Risk Appraisal Guide (VRAG) (Quinsey, Harris, Rice, & Cormier, 2006), HCR-20 (Douglas, Ogloff, Nicholls, & Grant, 1999; Douglas & Webster, 1999), and Classification of Violence Risk (COVR) (Monahan et al, 2005; Snowden, Gray, Taylor, & Fitzgerald, 2009; Steadman et al, 2000). Thus, clinicians providing mental health treatment to civilians now have at their disposal a substantial evidence-base evaluating risk of engaging in future violence (Heilbrun, 2009; Otto, 2009).…”
Section: Improving Risk Assessment Of Violence Among Military Veteranmentioning
confidence: 99%
“…Patients in category 1 have the lowest score and are considered to be at lower risk of violence than those patients in category 9 (Cooke et al ). Two studies by Doyle et al () and Snowden et al () found the VRAG with moderate predictive validity and significantly correlated with PCL‐SV and HCR‐20. As the PCL‐R/SV needs to be administered to obtain an overall VRAG score, the VRAG will, therefore, have similar practical implementation issues to the PCL‐R/SV in acute care setting.…”
Section: Resultsmentioning
confidence: 96%
“…For structured instruments to be of greatest use to clinicians, the violence rates for high-risk groups in different clinical settings and 31 Wormith (2007) 71 Snowden (2009) 68 Snowden (2007) 67 Seto (1999) 66 Rice (2002b) 65 Rice (2002a) 65 Rettenberger (2007) 64 Polvi (1999) 62 Morrissey (2007) 60 Mills (2006) 59 Looman (2010) 56 Kingston (2008) 50 Ho (2009) 48 Hill (2008a) 47 Helmus (2007) 46 Harris (2003b) 45 Harris (2003a) 45 Grann (2000) 42 Grann (1999) 43 Friendship (2003) 39 Eher (2009) 36 Eher (2008b) 37 Eher (2008a) 37 Douglas (2005a) 35 Dempster (2001) 33 Dempster (1998c) 32 Dempster (1998b) 32 Dahle (2006a) 29 Caperton (2005) 28 Bengtson (2008) 27 Beggs 2008 De Vogel (2004b) 31 Walkington (2006) 70 Viljoen (2008) 69 Reeves (2004) 63 Polvi (1999b) 62 Pedersen (2010) 61 Meyers (2008) 58 McEachran (2001) 57 Lodewijks (2008c) 55 Lodewijks (2008b) 54 Lodewijks (2008a) 53 Kropp (2000) 52 Kloezeman (2004)…”
Section: Discussionmentioning
confidence: 99%